Evolutionary Dynamics of Codon Usage Bias in Tomato Spotted Wilt Virus: Insights into Viral Adaptation and Host Interactions - Haiting Zhao; Lang Qin; Xiaolong Deng; Stuart Reitz; Shengyong Wu; Zhen He (Horticulturae, 2025)
Tomato spotted wilt virus (TSWV), belonging to the genus Orthotospovirus, is a significant pathogen through its infection of economically vital crops including tomato, tobacco, pepper, and other species worldwide. Given its substantial influence on the agricultural industry, in-depth research on TSWV is of great necessity. Several studies have been conducted on the dinucleotide preference of TSWV previously; however, the information regarding codon usage bias (CUB) and the virus’s adaptive evolution remains inconclusive. Here, a thorough analysis of TSWV was performed by utilizing five protein-coding sequences in order to investigate the characteristics of CUB. It has been observed that the TSWV protein-coding sequences are AU-rich, and codons ending with A or U are also preferred in these sequences. A consistently stable and preserved genomic composition characterized by a lower codon usage preference was also observed. Principal Component Analysis (PCA), neutrality analysis, and ENC-plot indicated that, in comparison to mutational pressure, natural selection has a more dominant influence on the CUB of TSWV. The codon adaptation index (CAI) demonstrated a more significant correlation between TSWV and Nicotiana tabacum. Meanwhile, the relative codon deoptimization index (RCDI) indicated a stronger correlation between TSWV and Solanum lycopersicum. This study is the first to systematically characterize the CUB of TSWV based on its protein-coding sequences, providing critical insights into viral genetic diversity, evolution mechanisms, and host adaptation. The findings advance understanding of plant-virus coevolution and inform virus-resistant crop breeding and antiviral strategies.